Identifikasi Nilai-nilai Religius melalui Pembiasaan Shalat Dzuhur Berjama’ah - Adawiyah, Sofiatul (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. This research aims to determine the form of identification of religious values through the habit of midday prayers in congregation, and strategies for cultivating religious values through the habit of midday prayers in congregation. This research uses a qualitative approach using descriptive methods that describe problems related to the topic to be researched using words and not numbers. This research uses observation, interviews, and documentation as data collection methods. Data analysis was carried out using data reduction, data modeling, and drawing conclusions. Data sources were obtained from PAI students and teachers at SMPN 1 Jenggawah. Based on research findings, the religious values that are instilled through the practice of midday prayers in congregation at SMPN 1 Jenggawah are the values of worship, moral values, example, discipline and social care. The strategy for instilling religious values through the habit of midday prayers in congregation at SMPN 1 Jenggawah is midday prayers which are held 4 days a week, Monday to Thursday according to the school schedule, coordinated by the teenage musollah of SMPN 1 Jenggawah, and prepared for attendance by the spiritual working group every class, example, invitation. Abstrak. Penelitian ini bertujuan untuk mengetahui bentuk identifkasi nilai-nilai religius melalui pembiasaan shalat dzuhur berjamaah, dan strategi dalam penanaman nilai-nilai religius melalui kebiasaan shalat dzuhur berjama’ah. Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan metode deskriptif yang menggambarkan permasalahan yang berkaitan dengan topik yang akan diteliti menggunakan kata-kata dan bukan angka-angka. Penelitian ini menggunakan wawancara, observasi, dan dokumentasi sebagai metode pengumpulan datanya. Untuk analisis data dilakukan dengan reduksi data, pemodela data, dan penarikan kesimpulan. Sumber data diperoleh dari siswa-siswi dan guru PAI di SMPN 1 Jenggawah. Berdasarkan temuan penelitian, bahwa nilai-nilai religius yang ditanamkan melalui pembiasaan shalat dhuhur berjama’ah di SMPN 1 Jenggawah ialah nilai ibadah, nilai akhlak, keteladanan, kedisiplinan, dan peduli sosial. Strategi dalam menanamkan nilai-nilai religius melalui pembiasaan shalat dhuhur berjam’ah di SMPN 1 Jenggawah adalah sholat dzuhur yang dilaksanakan 4 hari dalam seminggu, senin samapi kamis sesuai jadwal sekolah, dikoordinir oleh remaja musollah SMPN 1 Jenggawah, dan disiapkan absensi oleh pokja kerohanian setiap kelas, keteladanan, ajakan.